Iron Deposition Leads to Hyperphosphorylation of Tau and Disruption of Insulin Signaling - Wan, Wenbin; Cao, Lan; Kalionis, Bill; Murthi, Padma; Xia, Shijin; Guan, Yangtai (Frontiers in Neurology, 2019)
Iron deposition in the brain is an early issue in Alzheimer’s disease (AD). However, the pathogenesis of iron-induced pathological changes in AD remains elusive. Insulin resistance in brains is an essential feature of AD. Previous studies determined that insulin resistance is involved in the development of pathologies in AD. Tau pathology is one of most important hallmarks in AD and is associated with the impairment of cognition and clinical grades of the disease. In the present study, we observed that ferrous (Fe2+) chloride led to aberrant phosphorylation of tau, and decreased tyrosine phosphorylation levels of insulin receptor β (IRβ), insulin signal substrate 1 (IRS-1) and phosphoinositide 3-kinase p85α (PI3K p85α), in primary cultured neurons. In the in vivo studies using mice with supplemented dietary iron, learning and memory was impaired. As well, hyperphosphorylation of tau and disrupted insulin signaling in the brain was induced in iron-overloaded mice. Furthermore, in our in vitro work we identified the activation of insulin signaling following exogenous supplementation of insulin. This was further attenuated by iron-induced hyperphosphorylation of tau in primary neurons. Together, these data suggest that dysfunctional insulin signaling participates in iron-induced abnormal phosphorylation of tau in AD. Our study highlights the promising role of insulin signaling in pathological lesions induced by iron overloading.